Effect of Traditional and Software-Defined Networking on Performance of Computer Network - Sadiku, Isiaka Babatunde; Ajayi, Wumi; Sakpere, Wilson; John-Dewole, Temilola; Badru, R A (Universitas Negeri Semarang, 2022)
Purpose: Computer networks and the Internet are changing the way we communicate, learn, work, and even play. Conventional computer networks are not smart enough towards processes that contribute to improving online control transaction of services and demand for unlimited communication services. Hence, computer networking has to go smart.Methods: This paper explores the effect of different computer networking types - traditional computer networking (D0) and Software-Defined Networking (D1). The paper combined traditional computer networking (D0) with Software-Defined Network (D2) running applications (A1, A2, A3, A4 and A5) with the host sending 5 packets (P1, P2, P3, P4 and P5) across the networks emulated using Mininet network emulation to observe various performance parameters on the network.Result: It was observed that Application A1 recorded the highest bandwidth, throughput and latency. The least bandwidth, throughput and latency were observed in A4. The result showed that below 80% of the IPv4 packet size (65,507 bytes) of running application, the higher the bandwidth the higher the throughput. Also, the lower the latency the more statistically similar the jitter experienced. Packet P1 has the highest bandwidth and throughput usage with high latency. The results indicate that the higher the bandwidth and throughput, the higher the latency observed in the packet sent across the network. Traditional computer networking (D1) recorded the highest bandwidth and throughput with the highest jitter. The correlation result showed that the jitter decreases with increasing bandwidth and throughput.Novelty: This study provides information on traditional computer networking and Software-Defined Networking. The result validates studies that observed significant F-value and stability in the SDN application-awareness experiment.